2021
DOI: 10.1371/journal.pone.0257918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intradialytic exercise for advanced-age patients undergoing hemodialysis: A randomized controlled trial

Abstract: Previous reports have shown the benefits of intradialytic exercise to patients undergoing hemodialysis. However, most of those studies assessed the effects of exercise in middle-aged patients and little is known about advanced-age patients undergoing hemodialysis. Therefore, the present randomized controlled trial was performed to determine the effectiveness of exercise therapy in advanced-age patients undergoing hemodialysis. This non-blinded, randomized controlled parallel trial enrolled a total of 101 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
3
9
0
1
Order By: Relevance
“…In the OO patients, the relatively frequent cardiovascular and metabolic comorbidities may have lowered their functional adaptability to IRT 45 , 46 . This partially aligns with some previous reports on CKD-5D patients that found beneficial effects of exercise on MF in patients aged above 60 and 65 years 33 , 47 , 48 and with reports of no improvements in lower extremity muscle strength after intradialytic exercise in patients aged above 70 and above 80 years 49 , 50 . However, other studies reported no age-differences in functional adaptation after intradialytic- and home-based exercise in CKD-5D patients 19 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…In the OO patients, the relatively frequent cardiovascular and metabolic comorbidities may have lowered their functional adaptability to IRT 45 , 46 . This partially aligns with some previous reports on CKD-5D patients that found beneficial effects of exercise on MF in patients aged above 60 and 65 years 33 , 47 , 48 and with reports of no improvements in lower extremity muscle strength after intradialytic exercise in patients aged above 70 and above 80 years 49 , 50 . However, other studies reported no age-differences in functional adaptation after intradialytic- and home-based exercise in CKD-5D patients 19 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition to death, hospital transfer, hospitalization, surgery and other irresistible factors, 7 patients (7.7%) dropped out of the study due to loss of motivation, the proportion is lower than in previous studies. 38 , 39 During the first data collection, 2 patients were unwilling to continue the study because data collection occupied too much of their time. During the intervention, 5 patients lost motivation and dropped out of the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of improved physical function and nutritional status through exercise therapy and the factors associated with this improvement remain unclear. Some previous reports on intradialytic exercise have indicated a positive effect on exercise tolerance, gait function, and muscle strength, 7,8 while other studies have reported failure in improving physical function 9,10 . These studies that demonstrated difficulty in improving physical function despite exercise suggest that certain factors might affect the improvement in physical function and nutritional status.…”
Section: Introductionmentioning
confidence: 94%